2010
DOI: 10.1021/jf102572z
|View full text |Cite
|
Sign up to set email alerts
|

Time Course and Specificity of Lipolysis in Swiss Cheese

Abstract: Controlling lipolysis in cheese is necessary to ensure the formation of desirable flavor. To get a better understanding of the mechanism of lipolysis in Swiss cheese, cheeses were manufactured with and without (control) the addition of Propionibacterium freudenreichii. Products of lipolysis were quantified throughout ripening. Half of the free fatty acids (FFA) released in milk (3.66 mg/g fat), in particular the short-chain FFA, were lost in the whey during curd drainage, whereas diglycerides and monoglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…In Swiss-type cheeses, P. freudenreichii is the main agent of lipolysis (Chamba and Perreard 2002;Dherbécourt et al 2010). However, the intensity of lipolytic activity of P. freudenreichii, again, is highly strain-dependent.…”
Section: Formation Of Flavour Compounds By Propionibacteriamentioning
confidence: 97%
See 1 more Smart Citation
“…In Swiss-type cheeses, P. freudenreichii is the main agent of lipolysis (Chamba and Perreard 2002;Dherbécourt et al 2010). However, the intensity of lipolytic activity of P. freudenreichii, again, is highly strain-dependent.…”
Section: Formation Of Flavour Compounds By Propionibacteriamentioning
confidence: 97%
“…However, the intensity of lipolytic activity of P. freudenreichii, again, is highly strain-dependent. In experimental Swiss cheeses manufactured using five different strains of P. freudenreichii, the net increases in FFA concentrations ranged from 0.2 to 3-4 mg.g −1 cheese, compared to the control cheeses manufactured without propionibacteria (Chamba and Perreard 2002;Dherbécourt et al 2010;Thierry et al 2005). In a model medium supplemented with an emulsion of milk fat, 19 strains out of the 21 tested strains released FFA, with a net production of FFA ranging from 0.137 to 1915 mg.g −1 , whereas two strains did not display any detectable lipolytic activity (Abeijon Mukdsi et al 2014).…”
Section: Formation Of Flavour Compounds By Propionibacteriamentioning
confidence: 99%
“…The corresponding butA gene was detected in the C. variabile genome, indicating that the synthesis of 2, 3-butanediol might contribute to flavor generation of smear-ripened cheeses. Moreover, lipolysis plays an important role in the formation of cheese flavor in several cheese varieties, such as Swiss cheese [158], Hispánico cheese [159], Domiati cheese [160], and smear-ripened cheeses [87]. The quantification of the production of flavour compounds from fat during cheese ripening by the action of lipases and esterases indicated that lipolysis can reach up 20% in mould-ripened cheeses, such as Camembert [111].…”
Section: Discussionmentioning
confidence: 99%
“…Although cheese proteomics still remains in its infancy, current research reveals that there are numerous biochemical events and transformations of milk-derived proteins and lipids which take place in the cheese core during ripening [33,34]. It is now…”
Section: From Milk To Fermentated Dairy and Ripened Cheesementioning
confidence: 97%